Implementation Of Financial Management Policies At Bpkad Taliabu Island District - Nadila Adnan*; Fadly Ali Taslim; Suratno Amiro; Musdar Muhammad (Universitas Syiah Kuala, 2023)
This study aims to determine how the characteristics of problems, policies and environments on the implementation of financial management policies at the Regional Financial and Asset Management Agency of Taliabu Island Regency.This research uses qualitative research methods with a grounded theory approach. The results showed that the characteristics of the problem of implementing financial management policies at the Regional Financial and Asset Management Agency of Taliabu Island Regency are still difficult to communicate matters in financial techniques because the human resources in BPPKAD are still lacking and limited. The implementation of regional financial management policies at BKPSDM in the Taliabu Island Regency Government has been clearly stated in Law No. 33 of 2014. Community groups influence the policy implementation process both in the nature of supporting the program and those opposing the program.